The effect of bigger human bodies on future global calorie requirements - Lutz Depenbusch; Stephan Klasen (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Global food demand will see a rapid increase over the coming decades. Existing studies on future calorie demand consider mainly population growth and rising incomes. We add to the literature by estimating the effect of increases in human weight caused by rising BMI and height on future calorie requirements. We produce projections that are solely based on human energy requirements for maintenance of weight. We develop four different scenarios that affect this value and show that increases in human height and BMI could lead to an increase in global calorie requirements by 18.73 percentage points between 2010 and 2100 compared to a world where the weight per age-sex group would stay the same. These increases will particularly affect countries which are already facing higher rises in calorie requirements due to high population growth. The region most affected by this pattern is Sub-Saharan Africa.
Keywords: O13; J11; Q01; Q11; 330; world food demand; nutrition; global outlook; agricultural outlook